2019
DOI: 10.1055/s-0038-1675844
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Reconstruction of a Face Transplant Candidate

Abstract: Since 2005, facial transplantation has emerged as a viable reconstructive option for the most severe defects not amenable to conventional reconstructive techniques, with promising aesthetic and functional outcomes to date. Key facial subunits and midface structures such as the eyelids, lips, and nose are now able to be successfully replaced rather than reconstructed, enabling adequate functional outcomes in even the most extensive defects. However, even in cases of severe facial disfigurement, the decision to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Such variable dissemination underscores the difficulty of understanding a program's recipient selection criteria without a consistent location to access this information. Furthermore, only a few FT programs displayed recipient selection criteria on patient-facing websites, which may pose a barrier in the referral process for patients and their physicians 82 . A comprehensive study of the patient referral process found that most self-referrals resulted in immediate exclusion and only 1 of every 6 physician-referred candidates ultimately underwent transplantation 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Such variable dissemination underscores the difficulty of understanding a program's recipient selection criteria without a consistent location to access this information. Furthermore, only a few FT programs displayed recipient selection criteria on patient-facing websites, which may pose a barrier in the referral process for patients and their physicians 82 . A comprehensive study of the patient referral process found that most self-referrals resulted in immediate exclusion and only 1 of every 6 physician-referred candidates ultimately underwent transplantation 55 .…”
Section: Discussionmentioning
confidence: 99%
“…27 Significant tissue loss to the majority of the face is a strong indication for FVCA, as autologous reconstruction would not be as feasible given the lack of viable tissue in the face. 27 From a psychosocial standpoint, strong support systems and a lack of active psychiatric issues are further indications for the procedure. 27 Further contributing to donor scarcity is the fact that faces are not listed as a donation option in organ transplant registries.…”
Section: Discussionmentioning
confidence: 99%
“…27 From a psychosocial standpoint, strong support systems and a lack of active psychiatric issues are further indications for the procedure. 27 Further contributing to donor scarcity is the fact that faces are not listed as a donation option in organ transplant registries. Instead, those who wish to donate their face must separately indicate this on their form, as this process requires a separate authorization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations